2009
DOI: 10.1016/j.jtcvs.2008.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel Y-shaped extracardiac Fontan baffle using computational fluid dynamics

Abstract: The area-preserving 12-mm Y-graft is a promising modification of the Fontan procedure that should be clinically evaluated. Further work is needed to correlate our performance metrics with clinical outcomes, including exercise intolerance, incidence of protein-losing enteropathy, and thrombus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 38 publications
5
171
2
Order By: Relevance
“…Slight improvements in performance in terms of local fluid dynamics were demonstrated by the Y-TCPC model, with better flow distribution, greater efficiency and minor power losses both at rest and in exercise. Although such results are in line with the recent literature studies [7,19], the enhancement in clinical outcome brought by a Y-graft configuration is not yet demonstrated.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Slight improvements in performance in terms of local fluid dynamics were demonstrated by the Y-TCPC model, with better flow distribution, greater efficiency and minor power losses both at rest and in exercise. Although such results are in line with the recent literature studies [7,19], the enhancement in clinical outcome brought by a Y-graft configuration is not yet demonstrated.…”
Section: Discussionsupporting
confidence: 58%
“…Computational modelling, clinical observation and experimental studies have suggested that the geometry of the TCPC plays a key role in energy losses and fluid dynamics [2,4] and previous work has considered both offset and Y-shaped alternative designs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical techniques allow us to examine the effects of the geometry of the Fontan connection that plays an important role in the overall success of the surgery, and assess blood flow characteristics and energy losses associated with a given surgical design. There are numerous articles on the total cavopulmonary connection simulation (see, e.g., [7,11,22,25,26]) that do a very careful CFD analysis on complex patient-specific configurations in an attempt to answer some of these questions. Some of the earlier work in computational fluid dynamics applied to congenital heart disease compared energy loss in the standard "t" junction Fontan with the proposed "offset" model, and led to the adoption of the offset model as the currently preferred method [9,10,28,29].…”
mentioning
confidence: 99%
“…Incorporating human pulmonary morphometry data to determine the impedance of the downstream vascular trees with patient-specific resistances determined from catheterization data has emerged as a successful strategy, providing physiologically sound boundary conditions and successfully capturing patient-specific pressure levels and flow characteristics. 28,43 These types of boundary conditions also allow for the straightforward modeling of PVR reduction during exercise. 29,45 Moving Walls…”
Section: Outflow Boundary Conditionsmentioning
confidence: 99%